Stimuli‐Responsive Polyurethane Dispersions – Aqueous Auto‐Dispersion. Issue 12 (25th October 2018) - Gupta, Harshit; Texter, John
Abstract: We report a single‐pot synthesis of polyurethanes (PUs) in solvent that utilizes an hydroxyl imidazolium bromide salt (ionic liquid) as a chain terminating group. This material, after being desolvated under activation, spontaneously disperses in water to form auto‐dispersing polyurethane dispersions (PUDs). These PUDs comprise aggregates, that separate under further activation (sonication) to form sub‐micron to sub‐100‐nm dispersions that are stable. Their size changes during such (auto) dispersion processing are examined by dynamic light scattering. Anion‐dependent stimuli‐responsiveness is observed upon anion exchange. This stimuli‐responsiveness is based on imidazolium‐anion pair solubility changes induced by anion exchange. Dispersion destabilization can be induced by selection and anion exchange for particular "hydrophobic" anions. Film formation and wetting are observed to exhibit stimuli‐responsiveness to anion exchange. Coatings based on PUD comprising tripropylene glycol are less hydrophilic than coatings incorporating PEO‐based PUDs. Abstract :